Pengujian fixed bed gasifier dengan bahan bakar biomassa - Mahardika Azis Mohammad (Badan Kerja Sama Teknik Mesin Indonesia, 2019)
Currently, the human need for energy is growing larger, due to the increasing population. The dependence on fossil fuels can be seen from Indonesia’s energy usage. Nowadays, energy consumption is dominated by petroleum (46.9%), natural gas (21.9%), coal (26.4%), and other (4.8%). Therefore, to reduce dependence on fossil fuels, biomass can be used as alternative energy which is renewable. In addition, technology required to improve the combustion efficiency is necessary. To convert solid fuel into gas fuel is gasification process. In this research, the downdraft gasification type reactor was tested. In this test, results obtained are CGE (Cold Gas Efficiency) by 41.1% and the gas content of CO2 (2.98%), H2 (2.66%), N2 (66.99%), CO (15.71 %), CH4 (2.98%), H2S (0.15%) with an AFR of 2.47